Identifikasi Keragaman Genetik Gen 12S Ribomsom RNA Sebagai Penanda Genetik untuk Penentuan Spesies Kuskus (IDENTIFICATION OF GENETIC DIVERSITY 12SRRNA GENES AS GENETIC MARKER FOR DETERMINING SPECIES CUSCUS) - Widayanti, Rini; Wijayanto, Hery; Wendo, Woro Danur; Kunda, Rony Marsyal (Jurnal Veteriner; Vol 16 No 2 (2015), 2015)
Cuscus is marsupial’s animal (Phalageridae) which has limited spread in eastern Indonesia (Sulawesi,Maluku, Papua), Australia and Papua New Guinea. The ex-situ and in-situ conservation of cuscus undercaptivating condition is an alternative solution to protect cuscus from extinction. This study aimed todetermine nucleotide sequence and genetic markers on 12Sr RNA gene with sequencing method of eachspecies on three islands. Whole genome DNA was extracted from 17 samples of cuscus obtained fromdifferent habitats, Sulawesi (2 individual), Maluku (7 individual), and Papua (8 individual) according tothe protocol of Qiamp DNA Blood Mini Kit (Qiagen), and then it was used as template for amplificationof 12Sr RNA gene by using PCR. PCR product were then purified using column chromatography and wereused as template for sequencing reaction. Result sequencing of 12Sr RNA gene were analyzed usingMEGA program version 6. PCR product gives a result nucleotida of 958 bp according to databasegenebank, sequencing product gives result nucleotida of 896 bp and found of 105 different nucleotide sites.Filogram based on nucleotide sequences 12SrRNA gene from Sulawesi cuscus is Ailurops ursinus whereasthe cuscus from Papua and Maluku is Phalanger sp. and Spilocuscus maculatus species. Thirteen nucleotidasites were found, sites no 67 (A/G), 89 (G/C), 137 (T/C), 285 (G/A), 468 (T/C), 595 (T/C, 598 (T/C), 647 (T/C),654 (G/A), 665 (T/C), 769 (C/T), 874 (C/T), and 876 (A/G) which can be used as genetic marker betweenPhalanger genera from Papua and Maluku, and three nucleotida sites (sites no 127 (G/A), 481 (C/T), and885 (T/C) can be used as genetic marker between Spilocuscus genera from Papua and Maluku.
Keywords: possum, sequencing, nucleotide, 12SrRNA gene